Enhanced thermal stability of the thylakoid membranes from spruce. A comparison with selected angiosperms - Karlický, Václav; Kurasová, Irena; Ptáčková, Božena; Večeřová, Kristýna; Urban, Otmar; Špunda, Vladimír (Photosynthesis research, 2016)
Recently, we have found that thermal stability of photosystem II (PSII) photochemistry in spruce needles is higher than in other plants (barley, beech) cultivated under the same temperatures. In this work, temperature dependences of various characteristics of PSII organization were studied in order to obtain complex information on the thermal stability of PSII function and organization in spruce. Temperature dependency of circular dichroism spectra revealed by about 6 °C higher thermal stability of macrodomain organization in spruce thylakoid membranes in comparison with Arabidopsis and barley ones; however, thermal disintegration of light-harvesting complex of PSII did not significantly differ among the species studied. These results thus indicate that thermal stability of PSII macro-organization in spruce thylakoid membranes is enhanced to a similar extent as thermal stability of PSII photochemistry. Clear-native polyacrylamide gel electrophoresis of preheated thylakoids demonstrated that among the separated pigment-protein complexes, only PSII supercomplexes (SCs) revealed considerably higher thermal stability in spruce thylakoids as compared to Arabidopsis and barley ones. Hence we suggest that higher thermal stability of PSII macro-organization of spruce is influenced by the maintenance of PSII SCs in the thylakoid membrane. In addition, we discuss possible effects of different PSII organizations and lipid compositions on the thermal stability of spruce thylakoid membranes.
Keywords: chlorofyl a; fluorescence; Electrophoresis, Polyacrylamide Gel; ječmen (rod); Thermal stability; vysoká teplota; Thylakoids; Hot Temperature; Circular dichroism; tylakoidy; Photosystem II Protein Complex; Norway spruce; fotosystém II (proteinový komplex); chlorofyl; Picea; smrk; Circular Dichroism; Arabidopsis; Chlorophyll A; Fluorescence; Hordeum; Thylakoid membrane; elektroforéza v polyakrylamidovém gelu; Chlorophyll; cirkulární dichroismus; Photosystem II organization